Modes of space appropriation in the decorated caves of El Castillo and La Pasiega (Puente Viesgo, Cantabria, Spain). (December 2019) - Groenen, Marc; Groenen, Marie-Christine
Highlights: Joint analysis of subterranean spaces and iconographic themes is likely to highlight symbolic organisation of a decorated cave. In El Castillo, the stylistic and technical characteristics show that the decoration has been structured in small sets of motifs, each located in a specific sector. In La Pasiega, the thematic, stylistic and technical analysis indicates different decorated sets: Gallery A is to be considered as a deep cave, whereas Gallery B appears to be an open-air sanctuary. Abstract: The iconographic, formal and technical analysis of the decoration elements of El Castillo and La Pasiega (Cantabria) highlights a heterogeneous distribution of the main themes, with distribution logics that are very different in each of the caves. In El Castillo, the main themes appear in distinct sectors, each one containing a central area with a high density of motifs and an end that sets its limit. Consequently, the decoration appears as a mosaic formed of small sets of motifs. In contrast, using the same analysis criteria for the cave of La Pasiega shows that, besides motifs of the same type spread in the network space, there are more structured decorated sets. The set of Gallery A shows an increasing number of motifs from the beginning to the end of the sector, with a maximum density at the level of the back areas. In turn, the set of Gallery B comprises animal figures that stood out all the more to the viewers that they were illuminated by natural light. Whereas the decoration of Gallery A is organised in the manner of deep sanctuaries, the ornamentation of the Salle du Mégacéros of Gallery B falls rather in the logic of open-air sanctuaries.